SYSTEMATIC LITERATURE REVIEW: DEVELOPMENT OF SCRATCH MEDIA ON STATISTICS MATERIAL TO TRAIN COMPUTATIONAL THINKING ABILITIES USING THE CONTEXT OF PALEMBANG SONGKET - Tuti Tuti; Tika Dwi Nopriyanti; Allen Marga Retta (Indiktika : Jurnal Inovasi Pendidikan Matematika, 2025)
The rapid advancement of digital technology in education has strengthened the role of computational thinking as an essential competency in 21st-century mathematics and statistics learning. Scratch, a block-based visual programming platform, is widely used to promote interactive learning and enhance students’ problem-solving and computational thinking skills. However, research on developing Scratch-based learning media specifically for statistics, particularly those integrating local cultural contexts, remains limited. This study conducts a Systematic Literature Review (SLR) to examine research published between 2020 and 2025 in Google Scholar and Scopus. Using PRISMA guidelines, eight relevant articles were selected based on predetermined inclusion criteria. The findings show that Scratch-based learning media are generally valid, practical, and effective in improving students’ computational thinking skills, conceptual understanding, and overall learning outcomes. Despite these positive results, the use of Scratch in statistics education is still less explored compared to other mathematics topics. Moreover, the integration of local cultural elements, such as Palembang Songket, into Scratch-based statistics learning media is rarely discussed. Therefore, this review highlights the need and potential for developing culturally integrated Scratch-based media to create meaningful, contextual, and engaging statistics learning aligned with 21st-century educational demands.